2021
DOI: 10.1167/tvst.10.9.35
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Retinal Artery Angle and Visual Function in Eyes With Idiopathic Epiretinal Membrane

Abstract: Purpose This study investigated the relationship between retinal artery angle and visual function in eyes with idiopathic epiretinal membrane (ERM). Methods Ultra-wide field fundus imaging was conducted to analyze ERM and normal contralateral eyes. In addition to the logMAR visual acuity (VA) measurement, the average of the vertical and horizontal metamorphopsia scores (Mave) was measured using m-Charts for each eye. We calculated the retinal artery angle (Yugami correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Presumably, the change of retinal artery angle is influenced by various traction forces, such as AL elongation and eyeball expansion. Our hypothesis aligns with the studies 6 , 27 suggesting that retinal vessels become straightened and attenuated, leading to decreased vascular perfusion due to axial elongation and eyeball expansion in high myopia. In other words, straightened retinal vessels led to a change in YCAs, accompanied by a decrease in VDs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Presumably, the change of retinal artery angle is influenced by various traction forces, such as AL elongation and eyeball expansion. Our hypothesis aligns with the studies 6 , 27 suggesting that retinal vessels become straightened and attenuated, leading to decreased vascular perfusion due to axial elongation and eyeball expansion in high myopia. In other words, straightened retinal vessels led to a change in YCAs, accompanied by a decrease in VDs.…”
Section: Discussionsupporting
confidence: 91%
“…The retinal artery angle was defined as the angle between the supratemporal and the infratemporal vascular arches, with the optic disk as the vertex (named YCA). It was measured by the ImageJ system (version 2.0.0; National Institutes of Health, Bethesda, MD, USA) as suggested by Nagura et al 6 For the assessment of the angle YCA, we drew a circle with a radius of the distance between the fovea and optic disk center and determined the intersection points between the supratemporal and infratemporal major retinal artery and the drawn circle. Moreover, the angle between two intersections and the optic disk center in the eyes with high axial myopia was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagura et al. [ 24 ] reported that the YCA was smaller in the eyes with an epiretinal membranes than that in the contralateral eyes. They speculated that contraction of the retina secondary to stretching by the epiretinal membrane was responsible for the decrease in the YCA and deterioration in visual function.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the retinal artery angle in the participators’ eyes in accordance with the Yugami correlated angle (YCA) defined by Nagura et al. [ 24 ]. First, the distance between the optic nerve head (ONH) and the fovea was measured.…”
Section: Methodsmentioning
confidence: 99%